A general unified method for calculating fire resistance of CFST columns considering various types of steel and concrete. (1st November 2022) - Yu, Min; Hu, Xuan; Xu, Lihua; Cheng, ShanShan
Abstract: Due to the advantages of CFST structures, various types of steel (e.g., ordinary/high strength/stainless steel, etc.) and concrete (e.g., ordinary/high strength/ultra-high performance/recycled concrete, etc.) are used in them, and fire safety design is an indispensable part in the structural design of CFST. However, there is still a lack of a simple unified fire design method that can consider different materials and their combinations at the same time. Based on the unified calculation method of fire resistance of CFST based on average temperature proposed by the authors, this paper focuses on enhancing the generality and accuracy of the unified method, with specific attention paying to the prediction of material properties degradation effect and cross-sectional average temperature under fire. For the prediction of material properties degradation effect with considering various types of steel and concrete, two methods, namely the global equivalent method and the segmented equivalent method, are proposed to convert arbitrary temperature reduction factor models defined at material level to the corresponding equivalent models defined at CFST section level. After validating with various types of steel and concrete material properties reduction factor models given in the previous literature, it turns out that the equivalent models generated by the two methods can well approximate the temperature-induced degradation effect at CFST section level. As for the prediction of average temperature with considering various types of steel and concrete, an incremental calculation method to calculate the average temperature of steel tube and concrete core is proposed, which is compatible with various thermal property models for different types of steel and concrete without any intermediate conversion techniques. In the meantime, this incremental calculation method can be adopted for CFST members with or without protection and is also consistent with the temperature calculation formulas for steel structures given in Code. In conclusion, the improvements made in this paper can expand the application scope of the previously proposed unified method to various types of concrete materials and thus enhance the generality of the method. Highlights: A general calculation framework for the fire resistance of concrete filled steel tubular (CFST) columns is proposed. Two equivalent methods are proposed to compute the average-temperature-based equivalent material properties. Analytical solution to the average temperature is derived and the corresponding numerical algorithm is also given. Extensive experimental data of fire resistance of CFST columns is collected to validate the methods proposed in this paper.